Magnetostratigraphy and Palaeoclimatic Significance of the Late Pliocene Red Clay‐Quaternary Loess Sequence in the Lanzhou Basin, Western Chinese Loess Plateau - Benhong Guo; Tingjiang Peng; Hao Yu; Zhengchuang Hui; Zhenhua Ma; Xiaomiao Li; Zhantao Feng; Jia Liu; Shanpin Liu; Jun Zhang; Xiyan Ye; Chunhui Song; et al. (Geophysical Research Letters)
Abstract The history of red clay‐loess accumulation in the Chinese Loess Plateau (CLP) is the key to understanding the aridification history of the Asian interior and the uplift of the Tibetan Plateau. Here we present high‐resolution magnetostratigraphy and grain‐size records of a 265.7‐m‐long drill core of the red clay‐loess sequence at Gaolanshan in the Lanzhou Basin from the western CLP. Our results, combined with the loess‐paleosol stratigraphy and regional stratigraphic correlation, indicate that the most complete and continuous red clay‐loess sequence since ~3 Ma was first found in the western CLP, which is ~0.8 Myr older than the previously investigated Quaternary loess in the Lanzhou region, and the age of the oldest Lanzhou loess‐paleosol sequence is ~2.8 Ma. Consequently, the major enhancement of the aridification at 2.8 Ma in the Asian interior was primarily controlled by the uplift of the Tibetan Plateau and global cooling.